KONTRIBUSI MINAT BACA BUKU BERBAHASA INGGRIS TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA KELAS I SMAN 68 JAKARTA - Bambang Sutjipto (Perspektif Ilmu Pendidikan, 2006)
This research aims gathering data of reading interest in English books and learning achievement in English subject of the first year Senior High School student. Research methods employed is descriptif corellational methods. The population of the reasearch coverage all first year student in add classes with the average number of the student in each class is 45 student. The sample is choosen by simple random sampling. The form of the instrument to collect data is presented in Liked skill with variable (x) is reading interest in English books and variable (y) is the mark of English subject stated in the report. The research findings so that there is positive corellation between the two variable ( rhitung = 0,99 > r table = 0,312). R = r2 = 99,4% determine by variable x. It also concluded, there is positve corellation between reading interast and learning acvievement in English subject. The contribution of reading interest in English books to learning achievement is 99,4%.